การศึกษาการใช้นิทานอีสปเพื่อพัฒนาการอ่านภาษาอังกฤษเพื่อความเข้าใจ - ภัทรลดา วงษ์โยธา, ศราวุฒิ ศิริวัฒน์, (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2018)
The purposes of this study were to study and compare English reading ability using E-shop of Mathayomsuksa 3 students before and after the instruction, and to study students’ attitude towards teaching English reading comprehension using E-sop. The sample consisted of 31 students of Mattayomsuksa 3 at Khamkeannakorn School, Khonkaen Province, in the first semester of the academic year 2017. They were selected by purposive selection. The design of this research was a one-group pretest-posttest design. The research instruments included 10 lesson plans, an English reading ability test, and an attitude questionnaire. The findings were as follows; The students’ pretest and posttest mean scores on English reading ability were 5.84 or 29.19 percent and 16.10 or 80.48 percent respectively. The posttest score was higher than the criteria of 70 percent and it was significantly higher than that of the pretest. The students’ attitude towards teaching English reading comprehension using E-shop was at a very good level. Keywords: English reading through E-sop, Reading for comprehension, the attitudes